A method for preparing acetonitrile and co-producing methanol by ammoniating methyl acetate

Acetonitrile and methanol can be produced directly from methyl acetate and ammonia by coupling ester ammonolysis and amide dehydration nitrification reactions with titanium oxide catalyst supported on mesoporous silica. This solves the safety and high energy consumption problems of existing acetonitrile synthesis processes and realizes efficient, green and economical acetonitrile production.

CN123042001APending Publication Date: 2026-11-06NORTHWEST UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611342709.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-01
Publication Date
2026-11-06

AI Technical Summary

Technical Problem

Existing acetonitrile synthesis processes suffer from low safety, complex processes, high energy consumption, and high costs. In particular, the traditional route using methyl acetate as a raw material is energy-intensive and suffers from severe equipment corrosion.

Method used

A mesoporous silica-supported titanium oxide catalyst is used to produce acetonitrile and methanol in a gas-solid phase reactor by coupling ester ammonolysis and amide dehydration nitrification reactions, directly using methyl acetate and ammonia, byproducts of coal chemical industry, as raw materials. The catalyst's activity and selectivity are enhanced through functional partitioning design.

Benefits of technology

This technology enables efficient preparation of acetonitrile at low temperatures, simplifying the process, reducing energy consumption, improving resource utilization, ensuring high safety, and allowing the byproduct methanol to be recycled, thus forming an internal resource recycling system and reducing carbon emissions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123042001A_ABST
    Figure CN123042001A_ABST
Patent Text Reader

Abstract

This invention belongs to the field of chemical catalysis technology, specifically disclosing a method for preparing acetonitrile and co-producing methanol from methyl acetate via gas-solid phase catalytic amination. This method utilizes TiO₂ supported on mesoporous silica. x Nanoparticles serve as catalysts, using methyl acetate and ammonia, downstream products of coal chemical industry, as raw materials to achieve the efficient conversion of methyl acetate to high-value-added acetonitrile through gas-solid phase catalytic reaction, while simultaneously producing methanol. This process route is simple and efficient, with excellent catalyst performance, high acetonitrile selectivity, and the co-produced methanol can be directly recycled into the coal chemical industry chain, realizing internal material recycling and comprehensive resource utilization, and has good application prospects and potential for green and low-carbon development.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of chemical catalysis technology, and specifically discloses a method for preparing acetonitrile by amination of methyl acetate and co-producing methanol. Background Technology

[0002] Acetonitrile (CH3CN) is an indispensable key chemical in fields such as lithium battery electrolytes, semiconductor chip cleaning and photoresist removal, and biopharmaceutical synthesis. With the rapid development of strategic emerging industries such as new energy vehicles, high-end manufacturing, and biopharmaceuticals, the market demand for high-purity acetonitrile continues to grow, and the development of its green and efficient synthesis technology has significant industrial value and strategic importance.

[0003] Currently, the main industrial synthesis routes for acetonitrile include the propylene ammoxidation by-product method, the acetic acid ammoxidation method, and the ethanol ammoxidation method. Among these, the propylene ammoxidation by-product method is a strongly exothermic reaction (ΔH≈-515 kJ / mol), posing a risk of temperature runaway and potential loss of control. Essentially, it is a side reaction in the ammoxidation of propylene to acrylonitrile, with acetonitrile being separated and recovered as a by-product. Its production capacity is constrained by acrylonitrile market fluctuations, and the separation and purification process is complex, involving the handling of the highly toxic by-product hydrogen cyanide, placing extremely stringent requirements on equipment and process operation. The acetic acid ammoxidation method uses acetic acid and ammonia as raw materials, reacting at 360–420 °C in the presence of an alumina catalyst to synthesize acetonitrile in one step. This method has a high raw material consumption (approximately 1763 kg of acetic acid is required per ton of acetonitrile), and acetic acid severely corrodes equipment, leading to catalyst deactivation. The ethanol amination method uses ethanol and ammonia as raw materials, reacting them at approximately 420°C in the presence of copper-based or cobalt-based catalysts to produce acetonitrile. This reaction is a strongly endothermic process with high energy consumption, and the raw materials for ethanol largely depend on grain fermentation or coal-based synthesis routes, limiting the cost and supply stability of the raw materials. Each of these three traditional routes has inherent limitations such as strong dependence on raw materials, high energy consumption, equipment corrosion, or difficulties in product separation, making it difficult to simultaneously meet the requirements of economic efficiency and environmental friendliness.

[0004] In recent years, the downstream industrial chain starting with coal-based methanol has made significant progress. The technologies for methanol to dimethyl ether via etherification and dimethyl ether to methyl acetate via carbonylation have become increasingly mature, and methyl acetate has become an important platform compound in the coal chemical industry. Meanwhile, the widespread application of coke oven gas to ammonia synthesis technology has made ammonia an important byproduct of the coking industry chain. If acetonitrile can be directly produced from methyl acetate and ammonia, byproducts of coal chemical production, using local resources, while simultaneously co-producing methanol, it is expected to achieve synergistic value-added utilization of these two byproducts. The co-produced methanol can be recycled back into the system to participate in the etherification and carbonylation processes, forming a low-carbon process route with internal resource recycling. Compared to the existing multi-step indirect route of methyl acetate → hydrogenation → ethanol → ammoniation → acetonitrile, this can significantly shorten the reaction process and reduce unit operation energy consumption and carbon emissions.

[0005] Existing literature reports that the nitrification reaction of esters with ammonia mostly uses long-chain fatty acid esters as substrates to prepare fatty nitriles, while research reports on the direct preparation of acetonitrile from methyl acetate are scarce. Known catalyst systems (such as silica and thorium oxide) used in ester ammoniation reactions often require high temperatures above 500 °C, resulting in high energy consumption, and the catalyst activity and selectivity need improvement. The traditional route for preparing acetonitrile from methyl acetate involves first hydrolyzing it into acetic acid and methanol, then using acetic acid and ammonia as raw materials via acetic acid ammoniation to produce acetonitrile. This process is lengthy, energy-intensive, and acetic acid causes severe corrosion to equipment. Summary of the Invention

[0006] To address the technical problems of low safety, complex processes, high energy consumption, and high costs in existing acetonitrile synthesis processes, this invention provides a method for preparing acetonitrile from methyl acetate and ammonia via ammoniation coupled with dehydration nitrification. This method uses methyl acetate, a byproduct of coal chemical industry, as raw material, coupling the ester-ammoniation reaction with the amide dehydration nitrification reaction in the same reactor. Through functional partitioning design of the catalyst, raw material costs are reduced, the process flow is simplified, and methanol is co-produced. The catalyst employs mesoporous silica-supported titanium oxide, which provides a large specific surface area. The framework-doped metal atoms and titanium oxide nanoparticles serve as catalytically active components, synergistically enhancing the nitrification performance of the catalyst.

[0007] To achieve the above objectives, the present invention adopts the following technical solution: a method for preparing acetonitrile and producing methanol by ammonolysis of methyl acetate, wherein methyl acetate is reacted with ammonia to generate acetamide intermediate and methanol, and the reaction equation is shown in (1):

[0008] (1)

[0009] The generated acetamide further undergoes a dehydration and nitrification reaction to produce acetonitrile, as shown in equation (2):

[0010] (2) The overall reaction equation is shown in (3):

[0011] (3)

[0012] The catalyst for the reaction is mesoporous silica-supported titanium oxide.

[0013] Preferably, the titanium oxide is TiO2. x It exists in the form of nanoparticles, where x is 0 < x ≤ 2 and the particle size is 1 ~ 100 nm.

[0014] Preferably, the mesoporous silica is further doped with metal atoms, which are one or more of rare earth elements or transition metal elements Zr.

[0015] Preferably, the titanium oxide active component is introduced into the mesoporous silica support by one or more of the following methods: impregnation, deposition, precipitation, or in-situ loading.

[0016] Preferably, the reaction temperature is 200~500 °C and the reaction pressure is 0.1~2.0 MPa.

[0017] Preferably, the molar ratio of ammonia to methyl acetate is 1:1 to 30:1.

[0018] Preferably, the loading of the titanium oxide is 1 wt% to 30 wt% of the total mass of the catalyst.

[0019] Preferably, the metal atoms account for 0.1 mol% to 20 mol% of the molar amount of titanium oxide.

[0020] Preferably, the gas-solid phase reactor is a fixed-bed reactor, a fluidized-bed reactor, a moving-bed reactor, or a radial-bed reactor.

[0021] Preferably, the catalyst further comprises an auxiliary agent selected from one or more of alumina, zirconium oxide, cerium oxide, or lanthanum oxide.

[0022] A second aspect of this invention protects an acetonitrile prepared according to the above method and used to produce methanol.

[0023] Beneficial effects

[0024] (1) The raw materials are widely available and the resource utilization rate is high. This invention uses methyl acetate and ammonia, by-products of downstream coal chemical industry, as raw materials to directly produce high-value-added acetonitrile and co-produce methanol. The co-produced methanol can be returned to the industrial chain to participate in the etherification and carbonylation processes, forming an internal resource recycling system and significantly improving the comprehensive utilization value of by-products.

[0025] (2) Excellent catalyst performance and high acetonitrile selectivity. This invention uses mesoporous silica-supported TiO2. x As a catalyst, especially Zr-doped mesoporous silica-supported TiO2 x Catalysts, the ordered channels of mesoporous silica are beneficial to TiO2 x High dispersion and mass transfer; Zr doping introduces Lewis acid centers, enhancing the activation ability of ester carbonyl groups; TiO2 x Oxygen vacancies provide activation sites for ammonia molecules, accelerating the dehydration and ring closure of amides. The synergistic effect of these three factors endows the catalyst with excellent low-temperature activity and selectivity for the target product.

[0026] (3) Synergy between process safety and green development. This invention adopts a gas-solid phase catalytic endothermic reaction route, which fundamentally avoids the risk of strong exothermic runaway temperature in the propylene ammoxidation by-product method. Moreover, the entire process does not involve corrosive media or highly toxic by-product hydrogen cyanide, resulting in high operational safety. At the same time, the one-step gas-solid phase method significantly shortens the process compared to the traditional multi-step indirect route, and excess ammonia can be recovered and recycled, combining atom economy and environmental friendliness. Attached Figure Description

[0027] The following figures are for illustrative purposes only and are not intended to limit the scope of the invention, wherein:

[0028] Figure 1 This invention illustrates the technical route for synthesizing acetonitrile;

[0029] Figure 2 The flowchart of the reaction system for synthesizing acetonitrile according to the present invention is shown;

[0030] Figure 3 The gas chromatogram of the reaction products obtained in Example 1 of this application is shown;

[0031] Figure 4 The XRD characterization results of the catalysts in Examples 1-5 and Comparative Examples 3-6 of this application are shown.

[0032] Figure 5 The TEM images show the elemental (Ti, Zr) distribution characterization results of the catalysts in Examples 1-5 and Comparative Example 4, and Example 4.

[0033] Figure 6 The N2 adsorption-desorption isotherms of the catalysts in Examples 1-5 and Comparative Examples 3-6 of this application are shown.

[0034] Figure 7 The reaction performance results of Examples 1-5 and Comparative Examples 1-6 in this application are shown;

[0035] Figure 8 The reaction performance results of Example 6 in this application are shown; Detailed Implementation

[0036] To make the above-mentioned objectives, features, and advantages of this application more apparent and understandable, a detailed description of specific embodiments of this application is provided below. Many specific details are set forth in the following description to provide a thorough understanding of this application. However, this application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar modifications without departing from the spirit of this application. Therefore, this application is not limited to the specific embodiments disclosed below.

[0037] To facilitate understanding of the present invention, a more complete description of this application will be provided below with reference to relevant embodiments. Preferred embodiments of the present application are given below. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided so that a thorough and complete understanding of the disclosure of this application will be achieved.

[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the application.

[0039] As used herein, the terms "and / or," "or / and," and "and / or" encompass any one of two or more of the related listed items, as well as any and all combinations of the related listed items. These arbitrary and all combinations include any two related listed items, any more related listed items, or a combination of all related listed items. It should be noted that when at least three items are connected using at least two conjunctions selected from "and / or," "or / and," and "and / or," it should be understood that, in this application, the technical solution undoubtedly includes solutions connected by "logical AND," and also undoubtedly includes solutions connected by "logical OR."

[0040] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.

[0041] In this application, numerical ranges are referred to as continuous unless otherwise specified, and include the minimum and maximum values ​​of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values ​​of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are incorporated.

[0042] This document only specifically discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, just as any upper limit can be combined with any other upper limit to form an unspecified range. Furthermore, each individually disclosed point or single value can itself serve as a lower or upper limit and be combined with any other point or single value or with other lower or upper limits to form an unspecified range.

[0043] Unless otherwise specified, the temperature parameters in this application may be either constant temperature processing or processing within a certain temperature range. The constant temperature processing allows temperature fluctuations within the precision range controlled by the instrument, such as ±5 °C, ±4 °C, ±3 °C, ±2 °C, or ±1 °C.

[0044] In this document, the term "suitable" as used in phrases such as "suitable combination," "suitable method," and "any suitable method" refers to the ability to implement the technical solution of this application, solve the technical problem of this application, and achieve the expected technical effect of this application.

[0045] In this application, terms such as "further," "even further," and "particularly" are used to describe purposes and indicate differences in content, but should not be construed as limiting the scope of protection of this application.

[0046] In this application, "optionally," "optionally," and "optional" mean that something is optional, that is, it means that it is selected from either "with" or "without." If there are multiple "optional" entries in a technical solution, unless otherwise specified, and there are no contradictions or mutual constraints, each "optional" entry shall be independent.

[0047] In the description of the application, "multiple" means at least two, such as two, three, etc., unless otherwise explicitly specified.

[0048] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions. Unless otherwise specified, all technical features and optional technical features of this application can be combined to form new technical solutions.

[0049] Unless otherwise specified, the raw materials used in the following examples can be derived from commercially available sources or prepared using conventional processes in the art.

[0050] Characterization test conditions:

[0051] XRD analysis was performed using a Bruker D8 Advance X-ray powder diffractometer (Bruker GmbH, Germany) to analyze the crystal structure of the samples. Wide-angle testing conditions were: Cu target Kα rays, tube voltage 40 kV, tube current 40 mA, scan range 10–80°, step size 0.02°, scan rate 0.2 sec / step. Small-angle testing conditions were: Cu target Kα rays, tube voltage 40 kV, tube current 40 mA, scan range 0.5–5°, scan rate 0.5 ° / min.

[0052] TEM analysis was performed using a Tecnai G² F20 transmission electron microscope (Analysis and Testing Center) from FEI Corporation to analyze the microstructure, crystal structure, and high-resolution lattice imaging of the samples. The testing conditions were: thermal field emission electron gun, accelerating voltage 20–200 kV, point resolution 0.24 nm, line resolution 0.14 nm, and STEM resolution 0.2 nm. Single / double tilt sample holders could be used depending on the testing requirements, and observation and analysis were conducted using selected area electron diffraction (SAED) and high-resolution (HRTEM) imaging modes.

[0053] Elemental characterization analysis was performed using a Thermo Scientific Apreo S scanning electron microscope and its accompanying EDS energy dispersive spectroscopy system to qualitatively and semi-quantitatively characterize the elements in the sample at the micro-area level. The testing conditions were: accelerating voltage 15 kV, working distance 10 mm, energy dispersive spectroscopy acquisition time 60 s, and dead time controlled at approximately 35%.

[0054] The adsorption-desorption isotherm of nitrogen at 77 K was determined using a Micromeritics TriStar II Plus 3030 physical adsorption analyzer. Before measurement, each sample was degassed under vacuum at 200 °C for 8 h. The specific surface area was calculated using the Brunauer-Emmett-Teller (BET) model based on adsorption branch data with relative pressure (p / p0) in the range of 0.05–0.30.

[0055] This invention provides a method for preparing acetonitrile and methanol by ammoniation of methyl acetate, wherein methyl acetate and ammonia are subjected to ammonolysis of the ester and dehydration of the amide in a gas-solid phase reactor in sequence to produce acetonitrile and methanol.

[0056] In some embodiments, the methyl acetate is first vaporized by being pumped into the vaporization chamber by a high-pressure liquid pump at a flow rate of 0.001~0.1 mL / min and a vaporization chamber temperature of 60~250 °C, so that the methyl acetate raw material is completely vaporized, and then mixed with ammonia and carrier gas; preferably, the vaporization temperature is 120 °C.

[0057] In some embodiments, the carrier gas for the reaction is one or more of nitrogen, argon, or helium to transport the reactant gas, regulate the reaction space velocity, and stabilize the reaction atmosphere; preferably, the carrier gas for the reaction is nitrogen.

[0058] In some embodiments, the ammonia flow rate is 10-80 mL / min, and the carrier gas flow rate is 10-60 mL / min. The vaporized methyl acetate is mixed with ammonia and carrier gas in a specific ratio.

[0059] The liquid hourly space velocity used in this article refers to the liquid hourly mass hourly space velocity (WHSV), which is based on the mass of liquid methyl acetate passing through a unit mass of catalyst per unit time; the gas hourly space velocity refers to the gas hourly volumetric hourly space velocity (GHSV), which is based on the total gas flow rate passing through a unit mass of catalyst per unit time.

[0060]

[0061]

[0062] ρ is the flow rate of methyl acetate, and ρ is the density of methyl acetate. This represents the total gas flow rate, including ammonia and nitrogen.

[0063] In some embodiments, the liquid hourly space velocity (LHSV) of methyl acetate is 0.12–12 mL·g. -1 ·h -1 The gas hourly space velocity (GHSV) of ammonia and nitrogen is 3000~20400 mL·g -1 ·h -1 .

[0064] In some embodiments, the catalyst for the reaction is a mesoporous silica-supported titanium oxide. In this catalyst, the mesoporous silica support provides an open pore structure, which facilitates the diffusion of reactant molecules within the catalyst and the distribution of active components. The titanium oxide supported on the support surface serves as a catalytic active center, which can promote the formation of amide intermediates during the ammonolysis of methyl acetate by regulating the adsorption and activation processes of reactant molecules, and further promote the removal of hydroxyl groups and the dehydration and nitrification processes in the amide intermediates, achieving a synergistic coupling of the amidation and dehydration nitrification reactions. In this process, the synergistic effect between the mesoporous silica and the titanium oxide helps to improve the contact efficiency between the reactants and the active sites, promoting the formation of acetonitrile.

[0065] In some embodiments, the titanium oxide is TiO x It exists in the form of nanoparticles, where 0 < x ≤ 2. The particle size is 1~100 nm, preferably 5~10 nm.

[0066] In some embodiments, the loading of the titanium oxide is 1 wt% to 30 wt% of the total catalyst mass. When the mass fraction of titanium oxide is higher than 30 wt%, excess titanium oxide tends to accumulate on the surface of mesoporous silica, causing pore structure coverage, affecting the contact between reactants and active sites, and reducing the dispersion of active components, resulting in a decrease in catalytic performance. When the mass fraction of titanium oxide is lower than 1 wt%, the number of active centers on the catalyst surface is insufficient, which cannot effectively promote amidation and dehydration nitrification reactions, resulting in a decrease in acetonitrile formation efficiency.

[0067] In some embodiments, the mesoporous silica is further doped with metal atoms, which are one or more of rare earth elements or Zr. Doping with metal atoms can regulate the structure and surface properties of the mesoporous silica support, enhance the interaction between the support and the supported active components, facilitate the uniform distribution of the active components on the support surface, and improve the catalyst's structural stability and catalytic performance. Preferably, the doped metal is Zr. The introduction of Zr can regulate the surface structural characteristics of the mesoporous silica support, enhance the interaction between the support and the titanium oxide active components, promote the uniform dispersion of titanium oxide species on the support surface, improve the utilization efficiency of the active components, and thus improve the catalytic performance of the catalyst in the methyl acetate amination coupled with dehydration and nitrification reaction.

[0068] In some embodiments, the metal atoms account for 0.1 mol% to 20 mol% of the molar amount of titanium oxide.

[0069] In some embodiments, the mesoporous silica support is OMS (ordered mesoporous silica), for example, it can be SBA.

[0070] In some embodiments, the Zr-doped mesoporous silicon oxide supported on TiO x The catalyst is prepared as follows:

[0071] ① Synthesis of Zr-doped mesoporous silica: 4 g of triblock copolymer P123 was dissolved in 50 mL of 2M hydrochloric acid solution until the solution was clear, and then 3.738 g of tetraethyl orthosilicate was added. The mixture was stirred at 40 °C for 4 h, and then a certain amount of Zr(NO3)4·5H2O, determined according to the Si / Zr molar ratio, was added to the mixture. The mixture was then stirred at 40 °C for an additional 24 h, and then transferred to an autoclave for further crystallization at 100 °C for 48 h. After the above steps, the pH of the synthesis system was adjusted to 7–8 by dropwise addition of ammonia at room temperature, and then subjected to hydrothermal treatment again at 100 °C for 48 h. The final solid was collected by filtration, washed with water, dried at 60 °C, and calcined at 600 °C for 5 h.

[0072] ② TiO xPreparation of OMS catalyst: 1.6 g of OMS was weighed and placed in a round-bottom flask. 120 mL of anhydrous ethanol and 1 mL of deionized water were added sequentially, and the mixture was ultrasonically dispersed for 30 min to ensure complete and uniform dispersion. The flask was then fixed in an oil bath with a magnetic stir bar. A mixture of tetrabutyl titanate and anhydrous ethanol, determined by the Si / Ti molar ratio, was slowly added under stirring. A reflux condenser was installed, and the mixture was heated to 80 °C and refluxed for 4 h. After the reaction was complete, the mixture was filtered. The resulting solid was washed three times each with anhydrous ethanol and deionized water, dried, and then calcined in a muffle furnace to obtain Zr-doped mesoporous silica-supported TiO2. x catalyst.

[0073] In some embodiments, the catalyst further includes an additive selected from one or more of alumina, zirconium oxide, cerium oxide, or lanthanum oxide. The additive improves the composition and structure of the catalyst, forms a synergistic effect with the active component, and enhances the catalyst's thermal stability, mechanical stability, and anti-sintering properties, thereby improving the catalyst's stability and lifespan during continuous reaction processes.

[0074] In some embodiments, the catalyst is pretreated under a nitrogen atmosphere at a temperature of 300–500 °C for 1–6 h at a nitrogen flow rate of 10–60 mL / min. This process aims to remove moisture and air from the catalyst surface through nitrogen purging. In some embodiments, the molar ratio of ammonia to methyl acetate is 1:1 to 30:1. A molar ratio of ammonia to methyl acetate < 1:1 results in a lower reaction conversion rate; a molar ratio > 30:1 leads to a significant increase in the amount of unreacted ammonia after the reaction, resulting in an increased amount of ammonia requiring subsequent processing and recovery. This increases the operational difficulty and energy consumption of product separation, ammonia recovery, and purification processes, raising process operating costs and affecting the stability of continuous production.

[0075] In some embodiments, the reaction temperature is 200 °C to 500 °C, and the reaction pressure is 0.1 MPa to 1.0 MPa. When the reaction temperature is too low, the activation of methyl acetate and ammonia on the catalyst surface is insufficient, resulting in a low reaction rate. When the reaction temperature is too high, the tendency for side reactions and coke formation increases, which is detrimental to the stable operation of the catalyst. Controlling the pressure to 0.1 MPa to 1.0 MPa is beneficial. Reaction pressure has a certain influence on the mass transfer, adsorption, and surface reaction process of reactants on the catalyst surface. Appropriately increasing the reaction pressure is conducive to increasing the effective concentration of reactants on the catalyst surface, thereby promoting the adsorption and activation of reactants. However, when the pressure is too high, exceeding 1.0 MPa, a high degree of reactant and product coverage easily forms on the catalyst surface, which may cause active sites to be occupied and limit further conversion of reactants. It also hinders timely product desorption, thus affecting the reaction rate and the long-term stable operation of the catalyst. Pressure below 0.1 MPa weakens the adsorption and activation of reactants on the catalyst surface, leading to a decrease in the acetonitrile formation rate. Therefore, by controlling the reaction pressure, a balance can be achieved between reactant surface enrichment, active site utilization, and product desorption. Preferably, the reaction temperature is 300 °C and the reaction pressure is 0.1 MPa.

[0076] In some embodiments, the product collection includes condensing the product flowing out of the reactor outlet through a condenser to obtain a crude product liquid mixture containing acetonitrile, methyl acetate, methanol, acetamide, and water.

[0077] The product was analyzed by gas chromatography, and the reaction conversion X, acetonitrile selectivity S, and acetonitrile yield Y were calculated based on the following equations:

[0078]

[0079]

[0080]

[0081] In some embodiments, the gas-solid phase reactor is a fixed-bed reactor, a fluidized-bed reactor, a moving-bed reactor, or a radial-bed reactor. Preferably, the reaction is carried out in a fixed-bed reactor. Fixed-bed reactors have advantages such as low catalyst attrition and loss, lower requirements for catalyst mechanical strength, no need for fluidizing gas, low overall cost, and simple operation. In some embodiments, the mass ratio of quartz sand to catalyst in the fixed-bed reactor is 0.1:2 to 10:1.

[0082] The second aspect of this application protects an acetonitrile prepared by the above method and its co-production with methanol.

[0083] In the following examples, " / " represents load and "-" represents doping.

[0084] Example 1

[0085] (1) 0.3 g of 1TiO2 / 5Zr-SBA-15 (where 1 represents the TiO2 oxide loading of 1% of the total mass of the catalyst and 5 represents the metal atom doping of 5 mol% of the titanium oxide molar amount, the same applies to the following examples) catalyst was loaded into a fixed bed reactor and pretreated with nitrogen at 300 °C for 0.5 h.

[0086] (2) Using methyl acetate as raw material, the liquid hourly space velocity is 6 mL·g -1 ·h -1 The temperature of the vaporization chamber is 120 °C.

[0087] (3) A gas mass flow meter was used to set the ammonia-to-ester ratio to 3.5, and the gas hourly space velocity (HSV) of nitrogen and ammonia was 15000 mL·g. -1 ·h -1 It is then mixed with the vaporized methyl acetate and introduced into the reactor bed.

[0088] (4) The temperature of the fixed bed reactor is 300 °C and the pressure is 100 kPa.

[0089] (5) Collect the liquid product and perform gas chromatography analysis to calculate the conversion, selectivity, yield, and space-time yield. Catalytic performance results are as follows: Figure 7 As shown.

[0090] Example 2

[0091] The catalyst in Example 1 was replaced with a 5TiO2 / 5Zr-SBA-15 catalyst, while all other conditions remained unchanged. The catalytic performance results are as follows: Figure 7 As shown.

[0092] Example 3

[0093] The catalyst in Example 1 was replaced with a 10TiO2 / 5Zr-SBA-15 catalyst, while all other conditions remained unchanged. The catalytic performance results are as follows: Figure 7 As shown.

[0094] Example 4

[0095] The catalyst in Example 1 was replaced with a 20TiO2 / 5Zr-SBA-15 catalyst, while all other conditions remained unchanged. The catalytic performance results are as follows: Figure 7 As shown.

[0096] Example 5

[0097] The catalyst in Example 1 was replaced with a 30TiO2 / 5Zr-SBA-15 catalyst, while all other conditions remained unchanged. The catalytic performance results are as follows: Figure 7 As shown.

[0098] Example 6

[0099] The catalyst in Example 1 was replaced with 20TiO2 / SBA-15, and the fixed-bed reactor temperatures were changed to 280 °C, 290 °C, and 320 °C, respectively, while other conditions remained unchanged. The catalytic performance results are as follows: Figure 8 As shown.

[0100] Comparative Example 1

[0101] The catalyst in Example 1 was replaced with a TiO2 catalyst and packed into a fixed-bed reactor, with all other conditions remaining unchanged. The catalytic performance results are as follows: Figure 7 As shown.

[0102] Comparative Example 2

[0103] The catalyst in Example 1 was replaced with ZrO2 catalyst and packed into a fixed-bed reactor, with all other conditions remaining unchanged. The catalytic performance results are as follows: Figure 7 As shown.

[0104] Comparative Example 3

[0105] The catalyst from Example 1 was replaced with SBA-15 catalyst and loaded into a fixed-bed reactor, with all other conditions remaining unchanged. The catalytic performance results are as follows: Figure 7 As shown.

[0106] Comparative Example 4

[0107] The catalyst in Example 1 was replaced with 5Zr-SBA-15 catalyst and packed in a fixed-bed reactor, with all other conditions remaining unchanged. The catalytic performance results are as follows: Figure 7 As shown.

[0108] Comparative Example 5

[0109] The catalyst in Example 1 was replaced with 10Zr-SBA-15 catalyst and loaded into a fixed-bed reactor, with all other conditions remaining unchanged. The catalytic performance results are as follows: Figure 7 As shown.

[0110] Comparative Example 6

[0111] The catalyst in Example 1 was replaced with 15Zr-SBA-15 catalyst and loaded into a fixed-bed reactor, with all other conditions remaining unchanged. The catalytic performance results are as follows: Figure 7 As shown.

[0112] Performance evaluation

[0113] After separation by gas-liquid condenser and gas-liquid separator, the product was introduced into a gas chromatograph. Gas chromatographic analysis was performed using Fuli Chromatography (F-60) with SE-30 column, injection port temperature of 220 °C, detector temperature of 260 °C, column temperature: 60 °C for 1 min, then increased to 225 °C at 25 °C / min and held for 8 min. The reaction conversion rate and selectivity were calculated.

[0114] From the appendix Figure 1 It is known that coal is gasified to obtain syngas, which is further synthesized into methanol. Methanol is dehydrated to produce dimethyl ether, and dimethyl ether reacts with CO to undergo a carbonylation reaction to produce methyl acetate. In the traditional process, methyl acetate is first hydrogenated to produce ethanol, and then acetonitrile is prepared by ammonialation of ethanol. This invention uses methyl acetate from coal chemical industry as raw material and ammonia as nitrogen source to achieve a one-step ammonialation of methyl acetate to acetonitrile under the action of a catalyst, eliminating the hydrogenation to ethanol step in the traditional route and co-producing methanol. The methanol after the reaction can be recovered and reused through separation and returned to the methyl acetate preparation process for continued use, thereby forming a methanol cycle and realizing the high-value utilization of coal-based carbon resources and the resource utilization of by-products.

[0115] From the appendix Figure 4 The data show that small-angle XRD results indicate that Ti / SBA-15 and Ti / Zr-SBA-15 catalysts with different TiO2 loadings all retain obvious (100) diffraction peaks, and (110) and (200) characteristic diffraction peaks can be observed, indicating that the catalysts after Zr modification and TiO2 loading still maintain the typical ordered mesoporous structure of SBA-15; as the TiO2 loading increases, the intensity of the characteristic diffraction peaks of the mesoporous structure weakens, but no obvious collapse phenomenon of the mesoporous framework is observed, indicating that the TiO2 loading process can better maintain the mesoporous structure of the support. Wide-angle XRD results showed that SBA-15 and 5Zr-SBA-15 mainly exhibited amorphous silica characteristics. Catalysts with TiO2 loading of 1% to 10% did not show obvious TiO2 crystal phase diffraction peaks, indicating that the TiO2 active component could be well dispersed on the surface and in the pore structure of the Zr-SBA-15 support. As the TiO2 loading further increased, TiO2 crystal phase characteristic diffraction peaks gradually appeared in the high-loaded samples, indicating that the excess TiO2 began to aggregate and crystallize to a certain extent.

[0116] Table 1

[0117] catalyst <![CDATA[TiO₂ crystal phase]]> Particle size (nm) 30Ti / 5Zr-SBA-15 Anatase 13.7 20Ti / 5Zr-SBA-15 Anatase 6.0

[0118] Table 1 shows the titanium dioxide grain sizes of the catalysts in Examples 4 and 5 of this application, calculated using the XRD Scherrer formula. Estimated using the Scherrer formula, the average TiO2 grain sizes in 20Ti / 5Zr-SBA-15 and 30Ti / 5Zr-SBA-15 are approximately 6 nm and 13 nm, respectively. Samples without TiO2 diffraction peaks in XRD indicate smaller particle sizes (<~3 nm), suggesting they are TiO2. x Sub-nano clusters. As the TiO2 loading increases, the grains grow significantly, indicating that excessive loading easily causes TiO2 aggregation and crystallization, which is not conducive to the dispersion of active components.

[0119] Appendix Figure 5 TEM results showed that both the 5Zr-SBA-15 and TiO2-supported catalysts possessed relatively regular mesoporous channel structures. The overall pore structure of the support was maintained after TiO2 loading, and no obvious large-sized TiO2 particles were observed at appropriate loading levels. Deeper particle regions were observed in some areas of the highly loaded sample, consistent with the gradual appearance of the TiO2 crystalline phase in wide-angle XRD. Elemental distribution results showed that Zr and Ti elements were relatively uniformly distributed in the mesoporous silica support, without obvious local elemental enrichment, indicating that the mesoporous structure provides a good dispersion environment for the Zr and TiO2 active components.

[0120] Table 2 shows the N2 physical adsorption-desorption results. All samples exhibit typical Type IV adsorption isotherms and show obvious hysteresis loops in the medium-to-high relative pressure region, indicating that the samples all possess relatively obvious mesoporous structure characteristics. SBA-15 shows obvious capillary condensation in the p / p0 range of approximately 0.65-0.80, exhibiting typical H1-type hysteresis loop characteristics, consistent with the regular mesoporous structure of SBA-15. After introducing Zr and further loading Ti, all samples still retain obvious mesoporous adsorption-desorption characteristics, indicating that the loading process did not destroy the main mesoporous structure of SBA-15. However, the position and adsorption amount of the hysteresis loops changed to varying degrees, indicating that the introduction of Zr and Ti species had a certain impact on the pore structure of the material.

[0121] Table 2

[0122] catalyst <![CDATA[S BET (m 2 / g)]]> <![CDATA[V t (cm 3 / g)]]> <![CDATA[D avg (nm)]]> SBA-15 641 0.96 6.0 5Zr-SBA-15 330 0.91 11.0 10Zr-SBA-15 456 0.72 6.3 15Zr-SBA-15 444 0.72 6.5 1Ti / 5Zr-SBA-15 398 0.98 9.9 5Ti / 5Zr-SBA-15 397 0.76 7.6 10Ti / 5Zr-SBA-15 372 0.69 7.4 20Ti / 5Zr-SBA-15 363 0.50 5.5 30Ti / 5Zr-SBA-15 306 0.52 6.8

[0123] Referring to Table 2, which shows the specific surface area, pore volume, and average pore size of the catalysts in Examples 1-5 and Comparative Examples 3-6 of this application, it can be seen that the specific surface area and total pore volume of SBA-15 are 641 m². 2 / g and 0.96 cm 3 / g, with an average pore size of 6.0 nm. After Zr doping, the specific surface area of ​​the samples decreased, indicating that the introduction of Zr species changed the pore texture properties of SBA-15.

[0124] After further loading with Ti, the specific surface area of ​​the catalyst generally decreased with the increase of Ti loading. The above results indicate that with the increase of Ti loading, Ti species may gradually be distributed inside the SBA-15 channels or at the pore openings, occupying part of the channel space, thus leading to a decrease in the specific surface area and pore volume of the material. However, all samples still maintained obvious mesoporous adsorption-desorption characteristics, indicating that the modification of Ti and Zr did not lead to the complete destruction of the SBA-15 mesoporous structure.

[0125] In summary, the results show that Zr-modified mesoporous silica can promote the uniform dispersion of TiO2 active components while maintaining the ordered mesoporous structure of SBA-15. Under appropriate TiO2 loading, a relatively stable and well-dispersed TiO2 / Zr-SBA-15 composite catalytic structure can be formed, which is beneficial for sufficient contact between reactants and active components, and promotes the formation of amide intermediates during the ammoniation of methyl acetate and subsequent dehydration and nitrification reactions, thus achieving better acetonitrile production performance. Compared with the unmodified catalyst, the Zr-modified and titanium oxide-supported mesoporous silica catalyst exhibits superior catalytic performance in the ammoniation of methyl acetate to acetonitrile. The modified catalyst can effectively improve the conversion rate of methyl acetate and the yield of acetonitrile, indicating a synergistic effect between support modification and active component loading, which is beneficial for promoting the coupling of the amidation and dehydration and nitrification reactions. In different catalyst systems, the acetonitrile yield increased with increasing titanium oxide loading to 20%, then decreased at 30%. The catalyst with a 20% titanium oxide loading exhibited a higher acetonitrile yield and better reaction performance, and was therefore selected as the preferred catalyst system. Further investigation into the effect of reaction conditions on catalytic performance showed that within a certain range of temperature adjustment, the catalyst system could maintain good catalytic activity and achieve acetonitrile formation. However, when the reaction conditions deviated from the optimal range, both the methyl acetate conversion and acetonitrile yield decreased to varying degrees, indicating that rationally controlling reaction conditions plays a crucial role in improving reaction efficiency and the formation of the target product.

[0126] The above description of the embodiments is only for the purpose of helping to understand the method and core ideas of the present invention. It should be noted that those skilled in the art can make several improvements and modifications to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the protection scope of the claims of the present invention.

[0127] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A method for preparing acetonitrile by amination of methyl acetate and co-producing methanol, characterized in that, Methyl acetate and ammonia undergo a coupled reaction of ammonolysis and amide dehydration in a gas-solid reactor to produce acetonitrile and methanol. The catalyst for the reaction is mesoporous silica-supported titanium oxide.

2. The method according to claim 1, characterized in that, The titanium oxide is in the form of TiO x It exists in the form of nanoparticles, where 0 < x ≤ 2 and the size is 1 ~ 100 nm.

3. The method according to claim 1, characterized in that, The framework of the mesoporous silica is also doped with metal atoms, which are one or more of rare earth elements or transition metal elements Zr.

4. The method according to claim 1, characterized in that, The reaction temperature is 200~500 °C, and the reaction pressure is 0.1~2.0 MPa.

5. The method according to claim 1, characterized in that, The molar ratio of ammonia to methyl acetate is 1:1 to 30:

1.

6. The method according to claim 1, characterized in that, The loading of the titanium oxide is 1 wt% to 30 wt% of the total mass of the catalyst.

7. The method according to claim 3, characterized in that, The doped metal atoms account for 0.1 mol% to 20 mol% of the molar amount of titanium oxide.

8. The method according to claim 1, characterized in that, The gas-solid phase reactor is a fixed-bed reactor, a fluidized-bed reactor, a moving-bed reactor, or a radial-bed reactor.

9. The method according to claim 1, characterized in that, The catalyst also contains an auxiliary agent selected from one or more of alumina, zirconium oxide, cerium oxide, or lanthanum oxide.

10. An acetonitrile prepared by the method according to any one of claims 1 to 9, and a methanol-producing agent.